The gender gap. [article].
Stories like this sum up the ?motherhood penalty? to women?s careers. It is the main reason why the pay gap between men and women in rich countries is no longer narrowing. Employers view long hours as a sign of commitment and leadership potential. But from scarce, pricey child care to short school days, the world is organised for families with a parent at home?and that is usually the mother.